1
$\begingroup$

Evaluate:$$\displaystyle \lim_{x \rightarrow 0}\frac{\cos(1-\frac{\sin x}{x})+\cos(2-\frac{\sin(2x)}{x})+\cdots+\cos(k-\frac{\sin(kx)}{x})-k}{\cos(1-\cos(x))+\cos(2-2\cos(2x))+\cdots+\cos(k-k\cos(kx))-k}$$

I can find this limit using L' Hospital Rule, I do not know how to do it without that.This question is proposed to Romanian Math Magazine by Jalil Hajimir

$\endgroup$
3
  • 1
    $\begingroup$ I think there is a typo here $\cos(k-\color{red}k\cos(kx))$ $\endgroup$ – user Dec 4 '19 at 14:30
  • $\begingroup$ I fixed it. Thanks $\endgroup$ – Keon Dec 4 '19 at 15:00
  • $\begingroup$ Can you give a more precise reference (including a link, if there is one)? $\endgroup$ – Barry Cipra Dec 4 '19 at 15:17
1
$\begingroup$

Let's observe that $$\frac{1-\cos(j-j\cos jx)} {j^2(1-\cos jx) ^2}\to\frac{1}{2}$$ and hence $$\frac{1-\cos(j-\cos jx)} {x^4}=\frac{1-\cos(j-\cos jx)} {j^2(1-\cos jx) ^2}\cdot j^2\cdot\frac{(1-\cos jx)^2} {(jx)^4}\cdot j^4\to \frac{j^6}{8}$$ Thus if we change sign of both numerator and denominator of the expression under limit in question and divide both numerator and denominator by $x^4$ then the denominator of resulting expression tends to $\sum_{j=1}^{k}j^6/8$.

To deal with numerator let's observe that a typical term of numerator is $$\dfrac{1-\cos\left(j-\dfrac{\sin jx} {x} \right)} {x^4}=\dfrac{1-\cos\left(j-\dfrac{\sin jx} {x} \right)} {\left(j-\dfrac{\sin jx} {x} \right) ^2}\cdot\frac{(jx-\sin jx) ^2} {(jx) ^6}\cdot j^6\to\frac{j^6}{72}$$ and hence the numerator tends to $\sum_{j=1}^{k}j^6/72$. The desired limit is thus $1/9$. Note that we need here the result that $$\frac{x-\sin x} {x^3}\to\frac{1}{6}$$ which is easily handled via Taylor series.

$\endgroup$
0
$\begingroup$

Let proceed by Taylor’s series to obtain

$$\cos\left(k-\frac{\sin(kx)}{x}\right)=\cos\left(k-\frac1x\left(kx-\frac16k^3x^3+o(x^3)\right)\right)=$$

$$=\cos\left(\frac16k^3x^2+o(x^2)\right)=1-\frac1{72}k^6x^4+o(x^4)$$

and

$$\cos(k-k\cos(kx))=\cos\left(k-k\left(1-\frac12k^2x^2+o(x^2)\right)\right)=$$$$=\cos\left(\frac12k^3x^2+o(x^2)\right)=1-\frac18k^6x^4+o(x^4)$$

then

$$\frac{\sum_{i=1}^k \frac{i^6x^4}{72}+o(x^4)}{\sum _{i=1}^k \frac{i^6x^4}{8}+o(x^4)}= \frac{\sum_{i=1}^k \frac{i^6}{72}+o(1)}{\sum _{i=1}^k \frac{i^6}{8}+o(1)}\to \frac19 \frac{\sum_{i=1}^k i^6}{\sum _{i=1}^k i^6}=\frac19$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.